Basilan kitabs - Tan, Samuel K.; Hairulla, Munap H.; Ahajin, Majid N.; University of the Philippines. Center for Integrative and Development Studies (Quezon City University of the Philippines, Center for Integrative and Development Studies, 2007)
Collection of Tausug letters from Basilan on the Islamic beliefs.
In Tausug; with translation in English
Keywords: Jawi alphabet; Tausug (Philippine people) -- History -- Sources; Muslims -- Philippines -- History -- Sources; Tausug language -- Texts; Islam -- Philippines -- Sulu Archipelago